Determinants of circumcision and willingness to be circumcised by Rwandan men, 2010 - Gasasira, Rwego A.; Nsanzimana, Sabin; Mbabazi, Jennifer; Karema, Corine; Asiimwe, Anita; Mugwaneza, Placidie (BMC Public Health, 2010)
Male Circumcision (MC) has been recommended as one of the preventive measures against sexual HIV transmission by the World Health Organization (WHO). Rwanda has adopted MC as recommended but the country is a non-traditionally circumcising society. The objective was to explore knowledge and perception of Rwandan men on Male Circumcision (MC) and to determine the factors associated with the willingness to be circumcised and to circumcise their sons. This cross sectional study was conducted in 29 districts of Rwanda between January and March 2010. Data were collected using a structured questionnaire among men aged 15-59 years. The rate of MC was measured and its perception from respondents, and then the factors associated with the willingness to go for MC were analysed using multiple logistic regressions. A total of 1098 men were interviewed. Among respondents 17% (95% CI 14-19%) reported being circumcised. About three-quarter (72%) could define MC, but 37% of adolescent could not. Half of the participants were willing to get circumcised and 79% of men would accept circumcision for their sons. The main motivators for MC were its benefits in HIV/STI prevention (69%) and improving hygiene (49%). Being too old was the main reason (32%) reported by men reluctant to undergo MC and younger men were afraid of pain in particular those less than 19 years old (42%). The willingness to circumcise was significantly associated with younger age, living in the Eastern Province, marital status, and the knowledge of the preventive role of circumcision. Adolescents and young adults were more willing to be circumcised. It is critical to ensure the availability of pain free services in order to satisfy the increasing demand for the scale up of MC in Rwanda.